2020
DOI: 10.1021/acs.iecr.9b06549
|View full text |Cite
|
Sign up to set email alerts
|

Confinement Effects and CO2/CH4 Competitive Adsorption in Realistic Shale Kerogen Nanopores

Abstract: The knowledge of adsorption behaviors and mechanism of CO2/CH4 in organic matter is of great importance for CO2 geological sequestration with enhanced gas recovery in shale reservoirs. In this study, the adsorption behaviors and confinement effects of CO2/CH4 in realistic kerogen nanopores have been investigated by using the grand canonical Monte Carlo method. To represent realistic nanopores in the kerogen matrix, the inkbottle-shaped and slit-like nanopores were developed. The effects of temperature, pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 74 publications
1
28
0
Order By: Relevance
“…Fortunately, molecular dynamics (MD) simulations, originating from Newtonian mechanics to define the force and capture the corresponding motion trajectory of all the particles, make it possible to directly characterize and observe the dynamics behaviors of each atom or molecule at the nanoscale. Typically for shale nanopores flow, the multiple phases (e.g., water and methane) and radical ambient conditions (e.g., high pressure and temperature) can be easily taken account into MD simulations system, and, hence, a great deal of MD simulation studies have been performed to reveal the transport characteristics of shale gas within nanopores, providing important cognitions and fundamental frameworks for gas transport through shale nanopores. In this work, the authors attempt to present a comprehensive review on current advances of shale gas transport through microporous/nanoporous media from molecular perspectives, including molecular models, flow simulation strategies, and significant results.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, molecular dynamics (MD) simulations, originating from Newtonian mechanics to define the force and capture the corresponding motion trajectory of all the particles, make it possible to directly characterize and observe the dynamics behaviors of each atom or molecule at the nanoscale. Typically for shale nanopores flow, the multiple phases (e.g., water and methane) and radical ambient conditions (e.g., high pressure and temperature) can be easily taken account into MD simulations system, and, hence, a great deal of MD simulation studies have been performed to reveal the transport characteristics of shale gas within nanopores, providing important cognitions and fundamental frameworks for gas transport through shale nanopores. In this work, the authors attempt to present a comprehensive review on current advances of shale gas transport through microporous/nanoporous media from molecular perspectives, including molecular models, flow simulation strategies, and significant results.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Ho et al 33 showed that methane release in nanoporous kerogen matrices is characterized by a fast release of pressurized free gas (accounting for less than 50% recovery), followed by a slow release of adsorbed gas as the gas pressure decreases. There are still other related molecular‐level simulation studies on enhanced shale gas recovery by carbon dioxide and CO 2 sequestration in kerogen matrices of different maturity and porosity, see, for example 34‐40 …”
Section: Introductionmentioning
confidence: 99%
“…There are still other related molecular-level simulation studies on enhanced shale gas recovery by carbon dioxide and CO 2 sequestration in kerogen matrices of different maturity and porosity, see, for example. [34][35][36][37][38][39][40] Most molecular models treat the shale OM as a dense porous kerogen matrix. 9,10 Although kerogen is the abundant species in the OM, the OM also contains other compounds such as asphaltenes, resins, and dissolved species (typically hydrocarbons, water and carbon dioxide), where their absence may be mimicked by introducing dummy particles into the kerogen matrix.…”
mentioning
confidence: 99%
“…They attributed this behavior to the fluid curvature which is higher in the cylindrical pore than in slit pores. In the same vein, 141 studied the adsorption selectivity of CH 4 and CO 2 in realistic pore structures considering the surface roughness. They found that inkbottle-shaped pores enhance the selectivity of CO 2 / CH 4 compared to slit pores.…”
Section: ■ Atomistic Simulationmentioning
confidence: 99%